COVID-19 vaccination in children: a public health priority - Eduardo Jorge da Fonseca Lima; Robério Dias Leite (Elsevier, 2023)
Objective: Covid-19 had a direct impact on children's health. The aim of this review was to analyze epidemiological and clinical data, the consequences of the pandemic, and vaccination aspects in this group. Sources of data: The searches were carried out from January 2020 to November 2022, in the MEDLINE databases (PubMed) and publications of the Brazilian Ministry of Health and the Brazilian Society of Pediatrics. Summary of findings: Covid-19 has a mild presentation in most children; however, the infection can progress to the severe form and, in some cases, to MIS-C. The prevalence of the so-called long Covid in children was 25.24%. Moreover, several indirect impacts occurred on the health of children and adolescents. Vaccination played a crucial role in enabling the reduction of severe disease and mortality rates. Children and adolescents, as a special population, were excluded from the initial clinical trials and, therefore, vaccination was introduced later in this group. Despite its importance, there have been difficulties in the efficient implementation of vaccination in the pediatric population. The CoronaVac vaccines are authorized in Brazil for children over three years of age and the pediatric presentations of the Pfizer vaccine have shown significant effectiveness and safety. Conclusions: Covid-19 in the pediatric age group was responsible for the illness and deaths of a significant number of children. For successful immunization, major barriers have to be overcome. Real-world data on the safety and efficacy of several pediatric vaccines is emphasized, and the authors need a uniform message about the importance of immunization for all children.